2008
DOI: 10.1080/14756360701715422
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity of a new triterpenoid saponin from carthamus tinctorius linn

Abstract: , was isolated from the methanolic fraction of the roots of this plant by various colour reactions, chemical degradations and spectral analysis. Compound (A) showed anti-inflammatory activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Saponins are phytochemicals and natural glycosides with a wide range of pharmacological properties. The bioactive triterpenoid saponin, 3β- O -[β- d -xylopyranosyl(1→3)- O -β- d -galactopyra-nosyl]-lup-12-ene-28 oic acid-28- O -α- l -rhamnopyranosyl ester compound in methanolic fraction, was reported in roots of C. tinctorius [ 43 ]. Furthermore, recent studies reported two alkaloid–saponins compounds ( N -coumaroylserotonin and N -feruloylserotonin) in C. tinctorius seeds [ 20 ].…”
Section: Safflower Chemical Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saponins are phytochemicals and natural glycosides with a wide range of pharmacological properties. The bioactive triterpenoid saponin, 3β- O -[β- d -xylopyranosyl(1→3)- O -β- d -galactopyra-nosyl]-lup-12-ene-28 oic acid-28- O -α- l -rhamnopyranosyl ester compound in methanolic fraction, was reported in roots of C. tinctorius [ 43 ]. Furthermore, recent studies reported two alkaloid–saponins compounds ( N -coumaroylserotonin and N -feruloylserotonin) in C. tinctorius seeds [ 20 ].…”
Section: Safflower Chemical Compositionmentioning
confidence: 99%
“…-[β-d-xylopyranosyl(1→3)-O-β-d-galactopyra-nosyl]-lup-12-ene-28 oicacid-28-O-α-lrhamnopyranosyl ester compound in methanolic fraction, was reported in roots of C. tinctorius[43]. Furthermore, recent studies reported two alkaloid-saponins compounds (N-coumaroylserotonin and N-feruloylserotonin) in C. tinctorius seeds[20].…”
mentioning
confidence: 98%
“…324 Lupane saponins with known genins include stallatoside B and erucasaponin A from the cactus Stenocereus eruca 325 and a saponin from roots of Carthamus tinctorius. 326 Gouanic acids A 697 and B 698 from aerial parts of Gouania ulmifolia 327 and 1-epi-ceanothic acid 699 from Gleditsia sinensis 328 are 3(2/1)-abeo-lupane derivatives. Elephanmollen 700 is a D:C-friedolupane derivative from Elephantopus mollis that shows cytotoxic properties.…”
Section: Tetranortriterpenoidsmentioning
confidence: 99%
“…Saponins are known to have interesting activities, e.g., as anti-inflammatory and diuretic agents [1][2][3][4][5]. In addition, saponins inhibit the growth of certain types of tumors in animals, particularly lung and blood cancers, without killing normal cells [6,7].…”
Section: Introductionmentioning
confidence: 99%